2011
DOI: 10.1179/1362171810y.0000000031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HAZ cracks on fatigue resistance of resistance spot welded joints made of advanced high strength steels

Abstract: A method is reported with which heat affected zone (HAZ) cracks in a specific region of spot welded joints, made of advanced high strength steels, could be realised. The influence of HAZ cracks on the fatigue behaviour, which is the focus of the contribution, was studied by evaluating the stiffness characteristics as a function of the number of cycles N in comparison with crack-free specimens, i.e. by analysing HAZ and fatigue cracks on the specimen surface and the surface of fatigue fractures containing beach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…KEY WORDS: fatigue; resistance spot weld; high strength steel; electrode; corona bond. many studies on the fatigue strength of RSW joints have been conducted [7][8][9][10][11][12][13][14][15][16][17] including ultra-high-strength steels. In those studies, it has been reported that the static tensile shear strength of RSW joint increased with increasing yield strength of steel, while fatigue strength was insensitive to the yield strength of steel.…”
Section: Fatigue Behavior Of Resistance Spot Welded Steel Sheets Fabr...mentioning
confidence: 99%
“…KEY WORDS: fatigue; resistance spot weld; high strength steel; electrode; corona bond. many studies on the fatigue strength of RSW joints have been conducted [7][8][9][10][11][12][13][14][15][16][17] including ultra-high-strength steels. In those studies, it has been reported that the static tensile shear strength of RSW joint increased with increasing yield strength of steel, while fatigue strength was insensitive to the yield strength of steel.…”
Section: Fatigue Behavior Of Resistance Spot Welded Steel Sheets Fabr...mentioning
confidence: 99%
“…In the case of LME outer cracks, Gaul et al [5], Brauser et al [6], Kim et al [7] showed that the fatigue life of spot welds was not signicantly aected by the presence of the cracks. Choi et al [8] showed that small LME outer cracks (< 500 microns) in TRIP spot welds would not induce signicant loss of cross tension strength, absorbed energy and fatigue life, while longer crack could.…”
Section: Inner Cracks (Type C)mentioning
confidence: 99%
“…It should be noted that for the production of surface cracks in the weld area, a welding current near the splash limit has to be used. For more details regarding the production of cracked samples see 11…”
Section: Requirements and Test Conditionsmentioning
confidence: 99%
“…For investigating the influence of gaps on the fatigue behavior different upper loads F U were used, while for the cracked samples a constant upper load F U of 2.75 kN was selected. Recently, Gaul et al11, 12 have shown that the specimen stiffness change during the fatigue test correlates with the fatigue crack propagation. Therefore, the stiffness characteristics of specimens with and without a crack were used to show the influence of cracks on the fatigue strength.…”
Section: Requirements and Test Conditionsmentioning
confidence: 99%